2021
DOI: 10.7759/cureus.17494
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Rapid Development of Methicillin‑Resistant Staphylococcus aureus Mechanical Aortic Root Abscess Despite Appropriate Antibiotic Use

Abstract: A 74-year-old male with a past medical history of mechanical aortic valve replacement presented with abdominal pain and fever. Blood cultures revealed methicillin-resistant Staphylococcus aureus (MRSA) and the patient was started on target antibiotics. Initial transthoracic echocardiogram and transesophageal echocardiogram (TEE) did not show any vegetations or significant valvular regurgitation. No other sources of infection were identified. Five days after the initial TEE, a repeat TEE revealed new areas of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…It is relevant to mention that two patients had histories of aortic valve replacement [ 28 ], pacemaker, and hip prosthetic implantation [ 29 ]. Despite receiving antibiotic treatment, the first patient who had undergone aortic valve replacement seven years prior developed an aortic root abscess.…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…It is relevant to mention that two patients had histories of aortic valve replacement [ 28 ], pacemaker, and hip prosthetic implantation [ 29 ]. Despite receiving antibiotic treatment, the first patient who had undergone aortic valve replacement seven years prior developed an aortic root abscess.…”
Section: Reviewmentioning
confidence: 99%
“…Despite receiving antibiotic treatment, the first patient who had undergone aortic valve replacement seven years prior developed an aortic root abscess. The blood cultures revealed that the infection was caused by MRSA, highlighting the aggressiveness of this microbe and its association with aortic root abscess [ 28 ]. The other patient developed IE related to their intracardiac device implantation.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations